2020
DOI: 10.1101/2020.09.22.308981
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A synergistic core for human brain evolution and cognition

Abstract: A fundamental question in neuroscience is how brain organisation gives rise to humans' unique cognitive abilities. Although complex cognition is widely assumed to rely on frontal and parietal brain regions, the underlying mechanisms remain elusive: current approaches are unable to disentangle different forms of information processing in the brain. Here, we introduce a powerful framework to identify synergistic and redundant contributions to neural information processing and cognition. Leveraging multimodal dat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(97 citation statements)
references
References 55 publications
4
90
0
Order By: Relevance
“…On the other hand, nodal values covaried with genes enriched for trans-synaptic signaling, neuronal projection and the synaptic membrane. This aligns with recent findings that synaptic genes also colocalize with highly-synergistic regions of the brain, which have been suggested to be crucial for human cognitive evolution 60 .…”
Section: Genomic Patterning Of Network Growthsupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, nodal values covaried with genes enriched for trans-synaptic signaling, neuronal projection and the synaptic membrane. This aligns with recent findings that synaptic genes also colocalize with highly-synergistic regions of the brain, which have been suggested to be crucial for human cognitive evolution 60 .…”
Section: Genomic Patterning Of Network Growthsupporting
confidence: 91%
“…The enrichment analysis that accompanied our GNM takes a very different approach. As far as we are aware, this is the first study aiming to bridge models of whole brain organizational emergence and genetics in this way (for work using generative models, see refs 24,25,35,54,55 and work that integrates Allen Brain Atlas gene data with functional and structural brain imaging, see refs [56][57][58][59][60] ). Nodal costs covaried with genes enriched for highly costly metabolic processes, including catabolic processes, protein transport and cellular components centered around the ribosome and endoplasmic membranes.…”
Section: Genomic Patterning Of Network Growthmentioning
confidence: 99%
“…Focusing on Stage (ii), our previous work (Luppi et al, 2020a) identified which regions of the human brain are predominantly synergistic, and thus are most reliant on combining information from other brain regions. The key signature of workspace regions is to have a high prevalence of synergistic (compared to redundant) connections, and therefore the synergy-rich regions reported in (Luppi et al, 2020a) are ideally poised as GNW candidates. Here, we consider the architecture of the global workspace more broadly, and combine Integrated Information Decomposition with graph-theoretical principles to bring insights about processing stages (i) and (iii) (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…By applying a generalisation of PID to timeseries data - known as Integrated Information Decomposition (ΦID) (Mediano et al, 2019a) - to functional and diffusion MRI data, our previous work identified a set of brain regions that constitute a “synergistic core” supporting higher-level cognitive functions in the human brain - which we believe may play the role of the brain’s global workspace (Luppi et al, 2020a). This “synergistic global workspace” mainly comprises high-level prefrontal and parietal cortical regions whose network organisation is especially well-suited for global integration of information across the brain, which contrast with the modular and redundant interactions observed in sensorimotor areas (Luppi et al, 2020a). Building on these findings, it is natural to ask whether this synergistic workspace is related to human consciousness.…”
Section: Introductionmentioning
confidence: 99%
“…Subjectively, humans experience the world as an amalgamation (integration) of distinct sensory streams (segregation) ( Tononi, 2004 ). Neurobiologically, information processed in parallel by domain-specific systems must be brought together and integrated, in order to guide adaptive behaviour ( Dehaene et al., 2011 ; Dehaene and Changeux, 2011 ; Luppi et al., 2020 ). Evidence from previous neuroimaging studies indicates that LSD and other psychedelics, such as psilocybin, decrease the integrity of functional connectivity (FC) within resting-state networks (RSNs), but increase FC between normally distinct RSNs ( Carhart-Harris et al., 2016 ; Johnson et al., 2019 ; Müller et al., 2018 ; Roseman et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%